1979
DOI: 10.1111/j.1471-0528.1979.tb11248.x
|View full text |Cite
|
Sign up to set email alerts
|

CIRCULATING LEVELS OF PREGNANCY SPECIFIC β1 GLYCOPROTEIN IN PREGNANCIES COMPLICATED BY DIABETES MELLITUS

Abstract: Circulating levels of SP, were measured in 20 insulin dependent diabetic women during the third trimester of pregnancy. With one exception, SP, levels were between the 80 per cent confidence limits of the normal range. The exception was a patient who was delivered of a normal infant at 37 weeks but had consistently low levels of SP, from 32 weeks until delivery, suggesting a specific defect in SP, synthesis.PREGNANCY specific ( 3, glycoprotein (SP,) is one of a new generation of proteins recently isolated from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

1982
1982
1993
1993

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 12 publications
0
4
1
Order By: Relevance
“…In our study many peak SP, concentrations lay above the 97.5th centile of our normal range. This is in contrast to the findings of Grudzinskas et al (1979) but may in part be explained by differences in methodology. Our assay system appears to detect both a and p components of SP,.…”
Section: Discussioncontrasting
confidence: 97%
“…In our study many peak SP, concentrations lay above the 97.5th centile of our normal range. This is in contrast to the findings of Grudzinskas et al (1979) but may in part be explained by differences in methodology. Our assay system appears to detect both a and p components of SP,.…”
Section: Discussioncontrasting
confidence: 97%
“…These women gave birth to infants of normal birth weight and the placental weights did not differ from those of the reference population. In contrast, Grudzinskas et al [5] reported that insulin-depen dent pregnant women who delivered infants of normal birth weight had SPi values that were evenly distributed between the limits of the normal range. The same was found for 2 women with large-for-date infants.…”
Section: Discussionmentioning
confidence: 94%
“…However, in another study [5] no relation was found between SPi level and blood glucose, daily insulin dosage or duration of the diabetic disease. Further investigations are needed to clarify this matter.…”
Section: Discussionmentioning
confidence: 99%
“…1). A similar case has only been reported once [10], suggesting a rare and specific defect in the SPj synthesis, as both these women had normal HPL values. It is of interest to note that a similar rare deficiency has been reported for HPL in cases with a normal pregnancy and delivery.…”
Section: Discussionmentioning
confidence: 90%